Extrinsic motivation (Henry Stewart Talks, 2026)
Extrinsic motivation definition, Extrinsic vs intrinsic motivation, Types of extrinsic motivators, Expectancy and reinforcement theory, Effects and limitations of extrinsic motivation, Risks of overusing extrinsic rewards, Balancing extrinsic and intrinsic motivation, Strategies for effective extrinsic motivators